In for a penny, in for a pound? Exploring mutual endorsement effects between celebrity CEOs and corporate brands. Issue 2 (12th March 2018) - Scheidt, Stefan; Gelhard, Carsten; Strotzer, Juliane; Henseler, Jörg
Abstract : Purpose: While the branding of individuals has attracted increasing attention from practitioners in recent decades, understanding of personal branding still remains limited, especially with regard to the branding of celebrity CEOs. To contribute to this debate, this paper aims to explore the co-branding of celebrity CEOs and corporate brands, integrating endorsement theory and the concept of meaning transfer at a level of brand attributes. Design/methodology/approach: A between-subjects true experimental design was chosen for each of the two empirical studies with a total of 268 participants, using mock newspaper articles about a succession scenario at the CEO level of different companies. The study is designed to analyse the meaning transfer from celebrity CEO to corporate brand and vice versa using 16 personality attributes. Findings: This study gives empirical support for meaning transfer effects at the brand attribute level in both the celebrity-CEO-to-corporate-brand and corporate-brand-to-celebrity-CEO direction, which confirms the applicability of the concept of brand endorsement to celebrity CEOs and the mutuality in co-branding models. Furthermore, a more detailed and expansive perspective on the definition of endorsement is provided as well as managerial guidance for building celebrity CEOs and corporate brands in consideration of meaning transfer effects. Originality/value: This study is one of only few analysing the phenomenon of meaning transfer between brands that focus on non-evaluative associations (i.e. personality attributes). It is unique in its scope, insofar as the partnering relationship between celebrity CEOs and corporate brands have not been analysed empirically from this perspective yet. It bridges the gap between application in practice and the academic foundations, and it contributes to a broader understanding and definition of celebrity endorsement.